Evaluating the response of the PIPER scalable human body model across child restraining seats in simulated frontal crashes. (21st March 2018) - Maheshwari, Jalaj; Duong, Nhat; Sarfare, Shreyas; Belwadi, Aditya
Abstract: Objective: Booster seats ensure appropriate belt fit for children that a traditional vehicle seat belt cannot offer to small occupants. In this study, the responses of the PIPER 6-year-old human body model are compared to the traditional Q6 anthropomorphic test dummy (ATD). Methods: Eight frontal impact finite element simulations were run using 4 different child restraining systems on the FMVSS 213 test bench. Kinematics and kinetics were extracted and compared between the 2 child models. Results: The PIPER 6-year-old showed variation by 11.2 ± 14.1% (head resultant acceleration, G ), 20.4 ± 50.3% (chest resultant acceleration, G ), 272.9 ± 188.4% (chest displacement, mm), 24.8 ± 17.5% (maximum head excursion, mm), −31.5 ± 5.1% (neck force, Fz, N), −73.8 ± 2.8% (neck moment, My, N.m), and −60.4 ± 7.2% ( Nij ) compared to the Q6. However, the kinematics of both models were nearly similar. Conclusions: The PIPER model has a flexible neck and shows higher chest displacement compared to the Q6. We hypothesize that this is due to the inherent anatomical and mechanical differences between the human body model and the ATD model. More research is needed to explore these differences systematically.